The Soils of Ecuador (World Soils Book Series, 2018)
This is the first book to comprehensively discuss Ecuadorian soils. Richly illustrated, it provides information on the unique characteristics and distribution of these soils. Due to the influence of the Andes, which vastly modified the climate and parental materials, a relative small country like Ecuador has a wide variety of soil orders, rarely found in other countries. The country is divided into three distinctive regions by the Andes: The Coastal Plain, the Andean Highlands, and the Amazonia Region each with different soil development, influenced by the varying conditions in that region. It is also necessary to consider the Galapagos Islands as a separate region with a particular climate and parental material.